PENGGUNAAN MODEL PROJECT BASED LEARNING (PJBL) DALAM MENINGKATKAN KEMAMPUAN BERNALAR KRITIS PADA MATERI MENGKLASIFIKASIKAN INFORMASI WACANA MEDIA CETAK SISWA KELAS 5 SEKOLAH DASAR - Asna Mariatul Kibtiyah (Universitas Muria Kudus, 2022)
This study aims to improve critical reasoning skills on the material of classifying print media discourse information in 5th grade elementary school students by using a project based learning model. The type of research used is Classroom Action Research through 2 cycles with the instrument used is a critical reasoning rubric. The research subjects were students of grade 5C at SDN Pati Kidul 01. This study showed that in cycle 1 the total score of students was 227 points with an average score of 9.46 or 47.3%. Furthermore, in cycle 2 the total score of grade 5C students at SDN Pati Kidul 01 increased to 346 points with an average score of 14.42 or 72.1%. Thus, the use of the project based learning model has succeeded in increasing critical reasoning skills in classifying information about printed media discourse for 5th grade students of SDN Pati Kidul 01.